Geoecological assessment of mercury load in the impacted area of the thermal power plant of Seversk; Proceedings of SPIE; Vol. 10035 : Atmospheric and Ocean Optics: Atmospheric Physics - Lyapina E. E. Elena Evgenievna; Talovskaya A. V. Anna Valerievna; Shakhova T. S. Tatiana Sergeevna; Parygina I. A. Irina Alekseevna (Atmospheric Physics and Climate, 2016)
Title screen